Increasing HIV-Free Survival of Infants: Reorganizing Care Using Quality Improvement for the Optimal Health and Nutrition of HIV-Positive Women and Their Exposed Infants in Uganda. (28th June 2019) - Nsubuga-Nyombi, Tamara; Karamagi, Esther; Nabitaka, Linda; Namukose, Samalie; Calnan, Jacqueline; Nyakwezi, Sheila; Bachou, Hanifa; Oucul, Lazarus; Amoah, Aurora O.
Reorganizing service delivery to integrate nutrition and infant and young child feeding (IYCF) with prevention of mother-to-child transmission (PMTCT) is important for improving outcomes of HIV-positive mothers and HIV-exposed infants (HEIs). Quality improvement (QI) strategies were implemented at 22 health facilities. The percentage of HIV-positive pregnant women and lactating mothers who received IYCF counseling at each visit improved (45%-100%; mean = 93.1%, standard deviation [SD] = 15.5). Adherence to IYCF practices improved (70%-96%; mean = 92.4%, SD = 8.5). Mother–baby pairs receiving the standard care package improved (0%-100%; mean = 98.6%, SD = 22.6). The HEIs alive at 18 months and infected decreased (mean = 6.2%, SD = 4.8). Statistical significance of change was estimated using Fisher exact test and magnitude of change over time by calculating the odds ratio. For all indicators, improvement was rapid and significant ( P < .001), especially in the first 6 months of QI implementation. Using QI to integrate nutrition and ensure consistent and comprehensive PMTCT service delivery improved IYCF adherence and decreased transmission.